Psychological Dynamics of Early Childhood with Selective Mutism - Fahrunnisa, Fahrunnisa (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – Selective mutism in early childhood, although the incidence is not much, this condition can be a big challenge for professionals, teachers, and parents. This study aims to describe the psychological dynamics of early childhood with selective mutism.Design/methods/approach – This qualitative research uses a case study approach—data collection techniques with observation, interviews, and documentation. Data analysis uses data reduction, data presentation and conclusion drawing. Test the validity of the data by triangulation of sources. The participant of this study was a five-year-old girl diagnosed with selective mutism.Findings – Selective mutism is associated with anxiety problems and not a problem with cognitive abilities and language development. Lack of social stimulation in preschool years reinforces the symptoms of selective mutism. Parenting history in the form of a mother’s emotional condition, pattern attachments, parenting style and labels affect the appearance of symptoms of selective mutism.Research implications/limitations – This research has a narrow coverage area, so the study results are not intended to draw general conclusions or generalizations. However, the results of this study are expected to be used to understand similar cases.Practical implications – The study’s results are expected to help understand the psychology of children with selective mutism so that preventive and interventional ways can be formulated to reduce the symptoms.Originality/value – Further research is recommended to deepen further the quantitative validity of the relationship between children’s selective mutism and mothers with a history of baby blues syndrome.Paper type: Case study